Analisis Tindak Tutur Ilokusi Asertif dalam Film “Rumah Dinas Bapak” Karya Bobby Prasetyo - Muadzin Muadzin; Nurul Liza Aulia Rahmi; Shabira Millatina; Shalshabila Naela Azzahra; Yogiana Zahwa Walidaini; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Muhammad Noor Ahsin (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
A speech act is a medium to express an idea and emotion of a person. Speech acts have several types, one of which is illocutionary speech acts. One form of illocutionary speech acts is assertive speech acts. This assertive illocutionary speech act is found in everyday life, one of which is through movie media. The purpose of this research is to identify and describe the form of assertive illocutionary speech acts contained in the movie "Rumah Dinas Bapak" and to describe the purpose and meaning contained in the movie. The method used in this research is a descriptive qualitative and theoretical approach in the form of written or spoken words from individuals and observable behavior. The result of the research that has been done is that there are nine assertive illocutionary speech acts in the movie studied. "Apa jangan-jangan maling mas?" is one of the assertive illocutionary speech acts of speculating. The benefit of this research is that it helps readers improve their understanding of the intent and meaning contained in an utterance and apply them correctly in daily life.